Analysis Of The Financial Performance Of The East Java Provincial Government - Flanivolya Matulessy, Zaschia; Hanisa, Layla; Kustiwi, Irda Agustin (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This research aims to evaluate the financial performance of local governments in East Java Province using various financial metrics, such as independence ratio, efficiency ratio, effectiveness ratio, decentralization ratio, growth ratio, operational solvency, long-term and short-term solvency, service solvency, revenue variations regions and regional variations in spending. This research uses the Literature Review research method. The journals reviewed consisted of 12 journals. From the results of the review, based on Regional Income Variances and Regional Expenditure Variances which show good results; The Effectiveness Ratio shows that several regions were included in the very effective category, however during the pandemic several regions were included in the quite effective category; The Efficiency Ratio shows that most regions are included in the efficient category; The Growth Ratio in regional financial performance mostly shows that the PAD value is positive; The Independence Ratio shows that some regions show an instructive relationship pattern, while other regions show a consultative relationship pattern; Dependency Ratio: there are regions that show a high level of dependence and there are also regions that show a low level of dependence; The compatibility ratio of some regions shows that it is not yet balanced, while other regions show a balanced compatibility ratio; The Degree of Decentralization Ratio shows varied results; Financial Flexibility was not found to be different before and during the pandemic; Economic Analysis Some regions are included in the economic category; Operational Solvency is different before and during the pandemic; There is no difference in short-term and long-term solvency before and during the pandemic; Service solvency is no different before and during the pandemic.